2008
DOI: 10.1074/jbc.m804526200
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycosylation of Laminin-332 Regulates Its Biological Functions

Abstract: Laminin-332 (Lm332) is a large heterotrimeric glycoprotein that has been identified as a scattering factor, a regulator of cancer invasion as well as a prominent basement membrane component of the skin. Past studies have identified the functional domains of Lm332 and revealed the relationships between its activities and the processing of its subunits. However, there is little information available concerning the effects of N-glycosylation on Lm332 activities. In some cancer cells, an increase of ␤1,6-GlcNAc ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…At the molecular levels, it has been suggested that GnT-III and the bisecting GlcNAc play roles in cell adhesion and migration by altering the N-glycans in adhesion molecules and the extracellular matrix such as E-cadherin, laminin, and integrin (Gu & Taniguchi, 2008;Isaji et al, 2004;Kariya et al, 2008;Kariya, Kawamura, Tabei, & Gu, 2010;Kitada et al, 2001;Pinho et al, 2012Pinho et al, , 2011Sato et al, 2009;Yoshimura, Ihara, Matsuzawa, & Taniguchi, 1996;Zhao et al, 2006). The expression of GnT-III was found to be upregulated by E-cadherin-mediated cell adhesion.…”
Section: Biological Aspects and Implication In Cancermentioning
confidence: 97%
“…At the molecular levels, it has been suggested that GnT-III and the bisecting GlcNAc play roles in cell adhesion and migration by altering the N-glycans in adhesion molecules and the extracellular matrix such as E-cadherin, laminin, and integrin (Gu & Taniguchi, 2008;Isaji et al, 2004;Kariya et al, 2008;Kariya, Kawamura, Tabei, & Gu, 2010;Kitada et al, 2001;Pinho et al, 2012Pinho et al, , 2011Sato et al, 2009;Yoshimura, Ihara, Matsuzawa, & Taniguchi, 1996;Zhao et al, 2006). The expression of GnT-III was found to be upregulated by E-cadherin-mediated cell adhesion.…”
Section: Biological Aspects and Implication In Cancermentioning
confidence: 97%
“…Intriguingly, the functions of a number of these glycoproteins are affected by N-glycosylation outside of the nervous system. Thus, β 1,6 -branching GlcNAc modifications were found to modulate cell adhesion and cell motility by affecting the functions of laminin 332 and α3β1 integrins (Zhao et al 2006, Kariya et al 2008). Another example of a carbohydrate structure that can markedly affect molecular interactions is α 2,6 -sialylation.…”
Section: N-glycosylation In Neural Developmentmentioning
confidence: 99%
“…Similarly, tetraspanin CD82 with incomplete Nglycosylation exhibits an enhanced association with the α3 and α5 integrin subunits [45]. A modest association between Lm332 and α6β4 integrin mediated by galectin-3 through the N-glycans on both molecules promoted cell adhesion and migration on Lm332 as well as α6β4 integrin clustering on Lm332 [23,43]. Accordingly, an appropriate intermolecular interaction through N-glycan is important for the efficient cellular signaling and the following cellular function.…”
Section: Roles Of N-glycosylation On α5β1 Integrinmentioning
confidence: 99%
“…Most of the studies have identified the functional domains of Lm332 and revealed the relationship between its activities and the processing of its subunits [42]. In fact, N-glycans on Lm332 also affect its activities [43]. To examine the effects of N-glycans of Lm332 on its activities, we purified Lm332s from the conditioned media of GnT-III and GnT-V overexpressing MKN45 cells.…”
Section: Roles Of N-glycosylation On α5β1 Integrinmentioning
confidence: 99%